Accuracy of Cone-Beam Computed Tomography in Determining the Root Canal Morphology of Mandibular First Molars - Mokhtari, Hadi; Niknami, Mahdi; Mokhtari Zonouzi, Hamidreza; Sohrabi, Aydin; Ghasemi, Negin; Akbari Golzar, Amir (Iranian Endodontic Journal, 2016)
Introduction: The aim of the present in vitro study was to compare the accuracy of cone-beam computed tomography (CBCT) in determining root canal morphology of mandibular first molars in comparison with staining and clearing technique. Methods and Materials: CBCT images were taken from 96 extracted human mandibular first molars and the teeth were then evaluated based on Vertucci’s classification to determine the root canal morphology. Afterwards, access cavities were prepared and India ink was injected into the canals with an insulin syringe. The teeth were demineralized with 5% nitric acid. Finally, the cleared teeth were evaluated under a magnifying glass at 5× magnification to determine the root canal morphology. Data were analyzed using the SPSS software. The Fisher’s exact test assessed the differences between the mesial and distal canals and the Cohen’s kappa test was used to assess the level of agreement between the methods. Statistical significance was defined at 0.05. Results: The Kappa coefficient for agreement between the two methods evaluating canal types was 0.346 (95% CI: 0.247-0.445), which is considered a fair level of agreement based on classification of Koch and Landis. The agreement between CBCT and Vertucci’s classification was 52.6% (95% CI: 45.54-59.66%), with a significantly higher agreement rate in the mesial canals (28.1%) compared to the distal canals (77.1%) (P<0.001). Conclusion: Under the limitations of this study, clearing technique was more accurate than CBCT in providing accurate picture of the root canal anatomy of mandibular first molars. Keywords: Cone-Beam Computed Tomography; Root Canal Morphology; Root Clearing